Ovarian torsion as an emergency clinical entity - Gul, Evrim; Ucarel, Mustafa; Gul, Yeliz; Kavak, Salih Burcin (My University, 2020)
In this study, we aimed to evaluate the diagnostic characteristics of ovarian torsion cases. This study was conducted between December 2017 and December 2019 by examining the records of patients diagnosed with ovarian torsion in Fırat University Hospital at Emergency Department. Age, number of pregnancy and birth numbers and clinical (symptoms and findings) and laboratory parameters (hemoglobin, hematocrit, platelet and white blood cell count) supporting ovarian torsion were evaluated. Symptoms and symptoms such as preoperative nausea, vomiting, tenderness, defense and rebound presence were recorded. Ultrasonographic parameters (ovarian size, presence of ovarian cysts, peripheral sequenced follicles, presence of vascular flow in doppler ultrasonography, presence of free fluid in the pelvic region) were evaluated. Descriptive statistics were used in the statistical evaluation of the data. In this study, the following parameters of 15 patients were evaluated retrospectively. Mean age, 26.02±5.3 years; mean number of gravidas, 2,21±1.35, mean White blood cell count 13250±2600 (/L), mean hemoglobin and hematocrit values were 12.4±2.5 (gr/dL) and 35.0±4.2 (%) respectively. All patients with ovarian torsion had pelvic pain (100 %) and 61% had nausea and vomiting. The most prominent feature of the examination was defensive rebound with43% and tenderness with 76 %. Enlargement of ovarian (>5 cm) were present in 86 % of the patients and accompanying ovarian cysts and fluid in pelvis were found in 80 % of the cases. Additionally, in 73 % of the patients loss of blood flow on Doppler examination was observed. 5 cases (25 %) were single and 4 patients (25 %) had concomitant pregnancy. Three pregnants were in 1st trimester (7,9 and 13 weeks of gestation), one of them was 34 weeks of gestation. There is no clinical or laboratory findings specific to ovarian torsion. Therefore, all signs and symptoms of the patients should be carefully evaluated. Evaluation of the symptoms, clinical and laboratory findings together will increase the diagnostic accuracy.
Keywords: Kadın Hastalıkları ve Doğum; Acil Tıp; Sağlık Bilimleri ve Hizmetleri